2021
DOI: 10.24215/2422572xe086
|View full text |Cite
|
Sign up to set email alerts
|

Incidencia del uso de pantallas en niñas y niños menores de 2 años

Abstract: Aunque no existe consenso sobre las repercusiones de la digitalización en la salud y bienestar de niñas y niños, algunos estudios revelan la necesidad del acompañamiento adulto para seleccionar contenidos y establecer límites. Los bebés necesitan explorar el entorno para desarrollar habilidades cognitivas, sensoriales y lingüísticas. Como nuestra capacidad de adaptación aumenta a medida que maduramos, cualquier alteración temprana en el desarrollo ejecutivo repercute a corto, medio y largo plazo. El uso inadec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 17 publications
(25 reference statements)
1
5
0
1
Order By: Relevance
“…Regarding the rest of the media, on average, toddlers used them for less than an hour per day and most of the toddlers hardly used the Tablet and PC. Our results were similar to other studies (Cristia & Seidl, 2015 ; Tabullo & Gago-Galvagno, 2022 ; Simaes et al, 2022 ) that show that in this age range the usage of digital media is low, but it is more than the pediatrics associations’ zero screen recommendation for this age group (Melamud and Waisman 2019 ; Sas & Estrada, 2021 ; Schwarzer et al, 2021 ), and there is a tendency for screen use to increase in this population with age (Cristia & Seidl, 2015 ; Schwarzer et al, 2021 ). It is interesting to note that when media was used by toddlers, parents often shared in this activity.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…Regarding the rest of the media, on average, toddlers used them for less than an hour per day and most of the toddlers hardly used the Tablet and PC. Our results were similar to other studies (Cristia & Seidl, 2015 ; Tabullo & Gago-Galvagno, 2022 ; Simaes et al, 2022 ) that show that in this age range the usage of digital media is low, but it is more than the pediatrics associations’ zero screen recommendation for this age group (Melamud and Waisman 2019 ; Sas & Estrada, 2021 ; Schwarzer et al, 2021 ), and there is a tendency for screen use to increase in this population with age (Cristia & Seidl, 2015 ; Schwarzer et al, 2021 ). It is interesting to note that when media was used by toddlers, parents often shared in this activity.…”
Section: Discussionsupporting
confidence: 91%
“…However, other studies have shown positive contributions from the individual and shared use of the PC, since this type of screen requires greater visual-motor coordination and, in this age, requires the presence of an adult to accompany the activity (Tabullo & Gago-Galvagno, 2022). In this case, being such young toddlers, the associations could be negative because the content used on this type of device is not age-appropriate (Madigan et al, 2020;Sas & Estrada, 2021). However, it is necessary to highlight that the effect of PC on vocabulary was also observed after controlling for sociodemographic variables in the regression models, which reinforces the findings of other studies (Madigan et al, 2020;Medawar et al, 2023) and recommendations from pediatric societies to moderate consumption in early childhood (Melamud and Waisman 2019;Sas & Estrada, 2021;Schwarzer et al, 2021).…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations